WAYANG KULlT INOVATIF CENK BLONK LAKON SUTHA AMERIH BAPA OLEH DALANG I WAYAN NARDAYANA KAJIAN BENTUK DAN MAKNA - I Ketut Saba (Gelar : Jurnal Seni Budaya, 2010)
Wayang kulit (a shadow play) is one of the performing arts which has become firmly rooted in Indonesia. It is even known in many countries in the world. Like other performing arts, wayang kulit has undergone changes in accordance with the demand of the surrounding society. It is hard for the society to be fond of wayang kulit if it does not make changes because the competition of the entertainment world is very hard (through electronic media or live performance). Wayang  Cenk Blonk - as people call it - is a new phenomenon that emerged in recent years. The emergence of Wayang Cenk Blonk cannot be separated from the figure of I Wayan Nardayana. By his creativity  and innovation, his popularity is rising to greater heights and a new genre of Balinese wayang kulit performance with Ramayana story has come into existence. He has made a total change in the appearance of figures, story; dialogues, property, and music. The presence of wayang Cenk Blonk is proved to make a change in Balinese society so that it is not surprising that people love it very much. The data of the article on Wayang Cenk Blonk was collected through literature study,  interview, observation and an analysis on a commercial cassette entitled "Sutha Amerih Bapa". Wayang Cenk Blonk can match the entertainment instantly obtained from electronic media. I Wayan Nardayana is able to change the society's hunger for actual news into an interesting performance, giving guidance and entertainment through fresh jokes.Key words: wayang, Cenk Blonk, puppeteer, innovative